Dose verification of helical tomotherapy intensity modulated radiation therapy planning using 2D-array ion chambers - Xu, S (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, Malaysia, 2010)
PURPOSE: To investigate the clinical usage of dose verification of Helical Tomotherapy plans by using 2D-array ion chambers, and to develop an efficient way to validate the dose delivered for the patients during treatments. MATERIALS AND METHODS: A pixel-segmented ionisation chamber device, IMRT MatriXX™ and Multicube™ phantom from IBA were used on ten selected Tomotherapy IMRT/IGRT head and neck plans in this study. The combined phantom was set up to measure the dose distribution from coronal and sagittal planes. The setup of phantom was guided for verifying the correction position by pre-treatment Tomotherapy MVCT images. After the irradiation, the measured dose distributions of coronal and sagittal planes were compared with those from calculation by the planning system for cross verification. The results were evaluated by the absolute and relative doses as well as Gamma (γ) function. The feasibility of the different measuring methods was studied for this rotational treatment technique. RESULTS: The dose distributions measured by the MatriXX 2D array were in good agreements with plans calculated by Tomotherapy planning system. The discrepancy between the measured dose and predicted dose in the selected points was within ±3%. In the comparison of the pixel-segmented ionisation chamber versus treatment planning system using the 3 mm/3% γ-function criteria, the mean passing rates of 2 mm dose grid with γ-parameter ≤1 were 97.37% and 96.91%, in two orthogonal planes (coronal and sagittal directions), respectively. CONCLUSION: MatriXX with Multicube is a new system created for rotational delivery quality assurance (QA) and found to be reliable to measure both absolute dose and relative dose distributions, simultaneously. It achieves the goal of an efficient and accurate dosimetry validation method of the helical delivery pattern for the Helical Tomotherapy IMRT planning.